2017
DOI: 10.1242/jcs.207886
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activity of the Ghrelin receptor reduces surface expression of voltage-gated Ca2+ channels in a CaVβ-dependent manner

Abstract: Voltage-gated Ca 2+ (Ca V ) channels couple membrane depolarization to Ca 2+ influx, triggering a range of Ca 2+-dependent cellular processes. Ca V channels are, therefore, crucial in shaping neuronal activity and function, depending on their individual temporal and spatial properties. Furthermore, many neurotransmitters and drugs that act through G protein coupled receptors (GPCRs), modulate neuronal activity by altering the expression, trafficking, or function of Ca V channels. GPCRdependent mechanisms that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 65 publications
5
19
0
15
Order By: Relevance
“…partners at the plasma membrane, whereas β2a and β2e subunits are tethered to the plasma membrane through two palmitoyl side chains or nonselective electrostatic interactions, respectively (33)(34)(35)41). When α1 subunits are coexpressed with WT β subunits, all β subtypes showed partial or total membrane localization, consistent with previous experiments in native cells and recombinant systems (36)(37)(38). We could demonstrate significant association of the β1b and β3 subunits with α1B subunits at the plasma membrane since, when these membrane-localized β subunits were translocated and concentrated in punctate ER-PM junctions by rapamycin application, the α1B subunits went with them.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…partners at the plasma membrane, whereas β2a and β2e subunits are tethered to the plasma membrane through two palmitoyl side chains or nonselective electrostatic interactions, respectively (33)(34)(35)41). When α1 subunits are coexpressed with WT β subunits, all β subtypes showed partial or total membrane localization, consistent with previous experiments in native cells and recombinant systems (36)(37)(38). We could demonstrate significant association of the β1b and β3 subunits with α1B subunits at the plasma membrane since, when these membrane-localized β subunits were translocated and concentrated in punctate ER-PM junctions by rapamycin application, the α1B subunits went with them.…”
Section: Discussionsupporting
confidence: 90%
“…Unlike the β2 isoforms, β1b-FG and β3-FG were found both in the cytoplasm and plasma membrane in cells expressing Ca V α1B/ α2δ1 (SI Appendix, Fig. S4B), consistent with previous reports (36)(37)(38). We examined whether some of those β subunits were interacting with membrane α1B subunits.…”
Section: Resultssupporting
confidence: 78%
“…The GHSR-1a constitutive activity has also been shown to reduce presynaptic Cav2 currents and GABA release in hypothalamic and hippocampal neurons (50,51), by reducing the cell surface expression of Cav2 channels (52). Our results complement this observation, but work should be done to explore how the effects of the constitutive activity of the ghrelin receptor on the inhibitory and excitatory systems contribute to memory formation.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, we found that GHSR constitutive activity can also impair Ca V currents in a chronic, G i/o ‐ and Ca V β‐subunit‐dependent and voltage‐independent manner (Lopez Soto, ; Mustafá et al . ). The impairment of Ca V currents by GHSR constitutive activity is related to a decrease in Ca V channel density at the plasma membrane together with a concomitant increase in Ca V channel density at the endoplasmic reticulum and Golgi apparatus.…”
Section: Discussionmentioning
confidence: 97%